Dilation of a non-quasifree dissipative evolution - Várilly Boyle, Joseph C. (1981)
A semigroup evolution for the 1/2-spin which admits a conservative dilation is known to be governed by a Bloch equation in a standard form. Here we construct a conservative dilation directly from the Bloch equation, thus yielding an example of a dilation scheme for an evolution which is not quasifree. Moreover, we show that this conservative evolution is never ergodic in the non-quasifree case.